Organocatalytic oxidative dehydrogenation of aromatic amines for the preparation of azobenzenes under mild conditions - Ma, Hengchang; Li, Wenfeng; Wang, Jian; Xiao, Guanghai; Gong, Yuan; Qi, Chunxuan; Feng, Yunpeng; Li, Xiufang; Bao, Zhikang; Cao, Wei; Sun, Qiangsheng; Veaceslav, Caraus; et al. (Tetrahedron, 2012)
(Diacetoxyiodo)benzene used as stoichiometrically and catalytically in the preparation of azobenzenes under mild reaction conditions was developed. The metal-free oxidation systems demonstrated wide substituents tolerance, alkyls, halogens, and several versatile functional groups, such as amino, ethynyl, and carboxyl substituents are compatible well, and the corresponding products could be formed with good to excellent yields. In this disclosed method, the more large scale formation of azo compounds also could be carried out successfully. Of note that 3-ethynylbenzenamine applied as a very useful cross dehydrogenative partner, which coupled with different anilines, providing asymmetrical azo compounds with acceptable yields in one step under very mild reaction conditions. [Display omitted]